PERBANDINGAN TEKNIK PEMERAHAN ASI TANGAN DENGAN MANUAL BREAST PUMP TERHADAP KENYAMANAN IBU DAN KUALITAS ASI - Siti Sopiatun; Heda Melinda N Natapawira; Meita Dhamayanti (JOMIS (Journal of Midwifery Science), 2020)
The scope of exclusive breastfeeding is low caused by many factors, one of which is a working mother. The government supports the program of exclusive breastfeeding for mothers by promoting breastfeeding by expressed breast milk. Expressed breast milk can be done by hand and manual tools such as pump. Expressed breast milk can be influenced by mother’s experience and the pain at the time of expressing breast milk, this can lead to a sense of comfort. The differences in expressing techniques might lead to contamination of different bacteria and fungi. the purpose of this research is to analyze the differences in hand milking techniques and manual breast pump on the comfort of the mother and the quality of breast milk This was an observational study with cross sectional approach and conductive in Taman Sari district, Bandung. The samples were 35 mothers who fulfilled the inclusion and exclusion criteria. Mann Whitney, Wilcoxon and McNemar were used in examining mothers’ comfort and breast milk quality. The result of of comfort score showed 65.6 in hand expressed and 59.5 has in manual breast pump. There were several significant differences in expressing techniques to mothers’comfort (p = 0.046). Hand expressing were contaminated by yeast (60%), total mesophilic bacteria (20%), and enterobacter (17.1%). Manual breast pump was contaminated by yeast (80%), total mesophilic bacteria (8.6%), and enterobacter (20%). Breast milk quality in hand expressed was better than the manual breast pump (p = 0.032). It was concluded that hand expressed more comfortable and had better quality breast milk than manual breast pump techniques.